RANCANG BANGUN APLIKASI PENYEDIA LIAISON OFFICER BERBASIS WEB - Bimantoro, Wildan; Setyawan, Henry Bambang; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi Universitas Dinamika, 2020)
In carrying out an Event, the role of Human Resources (HR) is needed so that Event activities can run well, these roles are Event Organizer (EO) and Liaison Officer (LO). EO is an organization that is very instrumental in the world of MICE (meetings, incentives, conferences and exhibitions). Whereas LO is a temporary job in running the core of an Event. The task of LO is very important for the continuity and smoothness of event activities because LO is required to be able to do basic things such as broad insight, excellent communication with individuals and teams in an EO. The current problem is that EO has difficulty in recruiting to obtain LO due to the lack of information regarding LO profiles and portfolios, on the other hand LO itself has difficulty finding Event for a job. In overcoming these problems, a solution is given in the form of an application as a container that can bring EO and LO together in order to facilitate EO in the search, recruitment and selection of appropriate HR and assist LO in finding work. Based on the results of the implementation and evaluation of the Liaison Officer Provider Design Application Building, it can be concluded that this application can help EO in finding suitable HR by conducting a review of each LO profile to be recruited, and this application can help LO as a media for self-branding to EO to make it easier in getting a job. The user acceptance test results are 100% can be used as a whole function.